Dynamic IEEE 802.21 information server mesh architecture for heterogeneous networks. (2016) - Orozco, Ana Lucila Sandoval; García, Daniel Espino; Armas, Roberto González de; Fernández, Jesús Antonio Puente; Villalba, Luis Javier García; Buiati, Fábio Mesquita
The future wireless communications is expected to integrate different link layer technologies and to allow the most appropriate network to be selected depending on different criteria. Mobile nodes (MN) may want to discover neighbouring networks and detailed parameters before it moves into the coverage areas of the candidate networks, focusing on the optimisation of handover processes. In the IEEE 802.21 standard, a media independent information service (MIIS) is developed providing network information within a geographical area. However, the MIIS focuses on the static information (channel information, service provider name, network type supported, etc.). Dynamic information includes link-layer parameters such as available network resources, throughput, data rate, etc. This paper proposes a dynamic information server mesh architecture (DISMA) for realtime collection, discovery and sharing of dynamic network information. With DISMA, the MN is able to retrieve real-time dynamic information using a decentralised MIIS framework. Finally, this distributed approach generates an important advantage regarding the scalability and robustness if compared with the traditional centralised scheme. This paper also provides NS-2 simulation results and analytical models to prove the feasibility and performance of DISMA scheme.